ASUHAN KEBIDANAN PADA NEONATUS NY “S” DI RUMAH BERSALIN BUNDA PUJA TEMBILAHAN TAHUN 2019 - Nanda Ariska; Haryati Astuti (Jurnal Kesehatan Husada Gemilang, 2022)
Neonates is the first period of life outside the womb up to the age of 28 days. Infant mortality rate (Kemenkes, 2018) in Indonesia 185 / day, The Neonatal Mortality Rate 15 per 1000 live births. Based on The Public Health service Profile (2019) the number of neonate deaths in Indragiri Hilir Regency as many as 21 neonate deaths and a complete KN of 79.9% means that it has not reached the minimum service standar target. The purpose of neonate obstetrics care is to conduct examinations and find out as early as possible if there are health problems in neonates. This midwifery upbringing to provide care to the neonates of Mrs. "S" in Bunda Puja Tembilahan Maternity Home in 2019 using varney flow method and documented in soap form. From the results of visits conducted on July 16, 2019 to August 3, 2019 3 times, the neonatal first visit (11 hours) was conducted in RB, the neonatal second visit (4 days) and the neonatal third visit (20 days) was done at home. From the results of the implementation of the care there is a gap in theory and practice, namely the absence of SHK examination and nonconformity of the time of hb0 immunization on the neonatal first visit and no weight measurements on the second and third neonatal visits. It is expected that the orphanage will be able to pay attention and carry out every type of service in neonates and Bunda Puja Maternity House is expected to improve the quality of service on neonates by facilitating SHK inspection equipment or cooperating to more adequate facilities.